The Role of Pentahelix Collaboration in The Management of Satupam Tourism Village South Tangerang City - Suleman, Sean; Pujiastuti, Sri (Media Wisata, 2026)
This study arose from the gap between the enormous potential of Satupam Tourism Village and the weak system of collaboration between actors that should support its sustainable management. Satupam Tourism Village in South Tangerang City has enormous potential for the development of community-based educational and culinary tourism, but still faces various coordination challenges and limited support from stakeholders. This study aims to analyze the role of pentahelix collaboration involving the government, academics, business actors, communities, and the media, as well as to identify the factors that hinder the formation of effective collaborative governance in Satupam. The research method uses a descriptive qualitative approach with in-depth interviews, field observations, and documentation techniques. The results show that pentahelix collaboration in Satupam has begun to take shape but is still informal and not yet institutionally structured. The community and academia play the most active roles, while the government, business actors, and media still contribute only to a limited extent. The main obstacles include weak coordination, lack of policy and funding support, and low mutual commitment. The study concludes that the application of collaborative governance principles in Satupam is still in its early stages (initiating stage) and requires institutional strengthening and cross-sector communication to realize synergistic and sustainable collaboration.